The bioremediation of glyphosate in soil media by some newly isolated bacteria: The COD, TOC removal efficiency and mortality assessment for Daphnia magna - Korkmaz, Volkan; Yildirim, Numan; Erguven, Gokhan Onder; Durmus, Barbaros; Nuhoglu, Yasar (Elsevier, 2021)
In this study, the bioremediation capacity of three isolates of Bacillus aryabhattai, Pseudomonas azotoformans and Sphingomonas pseudosanguinis and their consortia at glyphosate added soil medium investigated via the reduction of chemical oxygen demand (COD) and total organic carbon (TOC) parameters in filtrate waters obtained from a designed bioremediation setup. Additionally, mortality assays were performed on the filtrate waters with model organism Daphnia magna. According to the results of the experiments, at the end of the 11 days, the highest COD reduction rate seen in media with S. pseudosanguinis as 92.1% while TOC rate was 69.13% in consortia media. While the mortality rate was 10, 10 and 5% on B, P and S application groups at the end of the 72th respectively, these rates were 100% in control group at the end of the 48th. According to the results obtained from bioremediation and mortality assessment, these bacteria can reach the high bioremediation rate one by one and in consortia media. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Glyphosate remediation; Bacteria; COD; TOC; D; magna